Valuation Errors and Initial Price Efficiency of NSE Listed IPOs - Singh, Inderpal; Nayyar, Anand (Indian Journal of Finance, 2017)
This paper examined the valuation errors and initial price efficiency of NSE (National Stock Exchange) listed IPOs. The main objective of the study was to determine whether the valuation errors occurred due to deliberate discount given by issuers or due to wrong valuation method used and also attempted to find out the determinants that impacted the performance of IPOs in the initial market. The research study was also aimed to analyze the impact of certain determinants on the performance of IPOs in the initial market. The study examined an initial sample of 151 IPOs listed on the National Stock Exchange over the period from 2009 up to 2016, but there were 31 IPOs that were not listed and traded on NSE. All data were collected from secondary sources, and the majority of the data were collected and extracted from IPO prospectuses. Other variables were collected from companies' websites. After these exclusions, our final sample consisted of 113 IPOs that had complete data on all the variables employed in multiple regressions, and the dependent variable was taken as offer price and independent variables taken were : sales, age of the company, issue size, MAR, net asset value, and debt - equity ratio. The study found the relation between valuation errors and deliberate discounting, and it was found that out of a total of 113 IPO companies, 67 of the IPOs were underpriced, 45 IPO companies were overpriced, and the remaining one IPO traded at its offer price at the end of the first trading day.